A record of Notostraca on Socotra Island and the importance of local conservation of the habitat - van Damme, Kay (Zootaxa, 2018)
The first record of Triops Schrank, 1803 (Crustacea: Branchiopoda: Notostraca: Triopsidae) from Socotra Island is presented herein. Besides Madagascar and the current note, the genus is unknown from Indian Ocean islands. A brief morphological exploration indicates that the Socotran Triops cf. granarius (Lucas, 1864) (trachyaspis form) belongs to an African clade within this widespread Old World species complex and not to T. granarius s.str. from East Asia. Detailed morphological and molecular revision of the poorly studied Middle Eastern and Northern African populations in comparison to East Asian populations are needed to understand this group and the phylogenetic position and status of the Socotran tadpole shrimp. Found in a single locality (the archeological site Eriosh) in the rapidly changing coastal plains on Socotra, together with other large branchiopods (endemic Anostraca and unidentified Spinicaudata), the insular Triops population and the regionally neglected temporary lake habitat deserve a special protection status from a biodiversity conservation perspective. Triops cf. granarius is hereby suggested as a local flagship species for the conservation of temporary pool habitats on the island.